Screen Recording Video in Virtual Learning During Covid-19 Pandemic: Students' Perspective - Lisa Suhayati; Haryati Haryati (VELES Voices of English Language Education Society, 2021)
The application of digital tools has been used in educational institution including universities to strengthen the material delivery. They can be beneficial tools in COVID-19 pandemic condition as teachers' assistance. Due to these issues, this study was conducted to determine students' perspective on the implementation of screen recording video in virtual learning activities during Covid-19 pandemic. This study involved 50 participants of the sixth semester students of English department of Universitas Pamulang. To obtain the data, the writers distributed a questionnaire consisting 10 questions and interviewed 4 questions to the students related to the implementation of virtual learning in COVID-19 pandemic situation. The data analysis reveals that the students have top four positive responses of screen video recording in virtual learning: enhancing the quality of learning, helping students learn more effectively, enhancing students’ learning experience, students-teachers' engagement, and flexible time and place. They also find that teachers' assistance and guidance are still absolutely needed however beneficial screen recording video is.